2001
DOI: 10.1111/j.1572-0241.2001.03752.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Colonic Telomerase in Ulcerative Colitis

Abstract: Colonic mucosal expression of telomerase is reduced in ulcerative colitis. Levels are low even in microscopically normal mucosa, suggesting that telomerase deficiency may contribute to the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Patients enrolled in earlier studies reporting a deficiency of colonic telomerase in UC had relatively quiescent disease with low inflammatory scores 15,28 . All of the present study patients with UC had active inflammation, with most admitted to hospital because of an aggravation of symptoms.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Patients enrolled in earlier studies reporting a deficiency of colonic telomerase in UC had relatively quiescent disease with low inflammatory scores 15,28 . All of the present study patients with UC had active inflammation, with most admitted to hospital because of an aggravation of symptoms.…”
Section: Discussionmentioning
confidence: 63%
“…We previously showed that telomerase was present in pancreatic juice from patients with chronic pancreatitis 14 . In contrast, other studies have reported a deficiency of colonic telomerase in UC, 15,28 suggesting that a lack of this enzyme may play a role in the pathogenesis of UC. Support for this comes from studies involving telomerase‐deficient knockout mice, 29 in which the absence of telomerase led to intestinal atrophy and ulceration, as well as areas of increased epithelial cell proliferation.…”
Section: Discussionmentioning
confidence: 91%
“…55 Telomerase deficiency has been detected in the histologically normal mucosa of patients with inflammatory bowel disease (cancer cells expressed high telomerase activity). 56 Losses of chromosomes in nondysplastic tissue in patients with ulcerative colitis were associated with telomere shortening and the appearance of anaphase bridges, especially in patients in whom cancer developed. 57 …”
Section: Telomere Attrition and Cancermentioning
confidence: 99%
“…Although the basics of the original telomere hypothesis remain valid, important variations exist. For example, certain highly proliferative human cells are capable of expressing low or transiently high levels of telomerase upon commitment to clonal expansion, apparently slowing the net rate of telomere loss and conferring an extended, but still ®nite lifespan to these cells (Bodnar et al, 1996;Hiyama et al, 1995b;Taylor et al, 1996;Usselmann et al, 2001;Weng et al, 1996Weng et al, , 1997 (Figure 2A, line b). Also, certain transformed human cells capable of inde®nite replication in culture are telomerase negative, and maintain unstable telomeres by an alternative lengthening pathway (Bryan et al, 1997).…”
Section: The Telomere Hypothesis Of Cell Aging and Immortalizationmentioning
confidence: 99%